Associations between circulating cardiovascular disease risk factors and cognitive performance in cognitively healthy older adults from the NuAge study - Koblinsky, Noah D.; Carmichael, Pierre-Hugues; Belleville, Sylvie; Fiocco, Alexandra J.; Gaudreau, Pierrette; Greenwood, Carol E.; Kergoat, Marie-Jeanne; Morais, José A.; Presse, Nancy; Laurin, Danielle; Ferland, Guylaine (Frontiers in Aging Neuroscience, 2023)
Introduction Cardiovascular disease risk factors (CVRFs) contribute to the development of cognitive impairment and dementia. Methods This study examined the associations between circulating CVRF biomarkers and cognition in 386 cognitively healthy older adults (mean age = 78 ± 4 years, 53% females) selected from the Quebec Longitudinal Study on Nutrition and Successful Aging (NuAge). Memory, executive function, and processing speed were assessed at baseline and 2-year follow-up. CVRF biomarkers included total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), triglycerides, glucose, insulin, high sensitivity C-reactive protein (hs-CRP), homocysteine, protein carbonyls, and cortisol. Linear mixed models were used to determine associations between individual CVRF biomarkers and cognition at both time points. Results HDL-C was most consistently associated with cognition with higher values related to better performance across several domains. Overall, stronger and more consistent relationships between CVRF biomarkers and cognition were observed in females relative to males. Discussion Findings suggest that increases in the majority of circulating CVRFs are not associated with worse cognition in cognitively healthy older adults.